ANALISIS KESEHATAN KEUANGAN PD. BKK BREBES DI KABUPATEN BREBES - Medi Tri Purwanto (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
ABSTRAK This study aims to: to determine the health level of PD. BKK Brebes in Brebes Regency in terms of CAEL (Capital, Assets, Earnings and Liquidity) for the period 2013 - 2017. From the results of the analysis it can be concluded: based on the results of the analysis and discussion it is known the health level of PD. BKK Brebes in Brebes Regency in 2014 increased by 2.07 percent. In 2015, it decreased by 0.42 percent, in 2016 it increased again by 2.99 percent and in 2017 it increased by 0.30 percent. Based on the criteria set by Bank Indonesia, from 2013 to 2017 PD. BKK Brebes in Brebes Regency was declared PD. Healthy BKK. Overall health level of PD. BKK Brebes in Brebes Regency from 2013 to 2017 was declared healthy. Keywords: CAMEL, Bank Health